SUSTAINABILITY STATUS OF MANAGEMENT TERUBUK FISH (Tenualosa macrura) IN BENGKALIS DISTRICT - Rival Junaidi; Deni Efizon; Adriman Adriman (Asian Journal of Aquatic Sciences, 2022)
This research was conducted from July to October 2021 in Bengkalis Regency. This research is focused on evaluating in detail the condition of the ultimate fisheries from the ecological, social, economic, and institutional aspects as well as scientific information for follow-up planning and implementation of the best fisheries management in the waters of the Bengkalis Strait. The research method used during the study was a survey method. Types and sources of data used in this study are primary data and secondary data. The number of key respondents used in this study were 30 people. Sustainable fisheries management is seen from five dimensions, namely the ecological dimension, the economic dimension, the social dimension, the technological dimension and the institutional dimension. The scores for each attribute were analyzed using the Rapfish technique and will be passed through several analyzes such as multi-dimensional scaling (MDS), leverage analysis (JackKnife), and Monte Carlo analysis. Based on the results of the study the results of the catch of the terubuk fish during the period June-September amounted to 160 fish. From this amount, it showed that the percentage of male fish caught was much more dominant, namely 110 fish (69%) than 50 female fish (31%). The results of the analysis of each dimension show that the ecological index (59.92%) is included in the moderately sustainable category, the economic dimension (52.94%) is included in the moderately sustainable category, the social dimension (50.54%) is included in the moderately sustainable category, the social dimension (50.54%) is included in the moderately sustainable category. Institutional (49.91%) is included in the sustainable category and the technological dimension (70.25%) indicates the category is quite sustainable. Thus, the design of the terubuk fish management in Bengkalis waters can use the dimensions of the attributes that are classified as quite sustainable, to support or improve the institutional dimensions in order to support the management of terubuk fish